Edge-to-face stacking non-fullerene small molecule acceptor for bulk heterojunction solar cells. (September 2016) - Wu, Qichao; Li, Ling; Hai, Jiefeng; Zhang, Xin; Lu, Zhenhuan; Yang, Jianwen; Liu, Yongping; Zhang, Lingzhi; Zhan, Chuanlang
Abstract: Synthesis of a novel small molecule accepter with perylenediimide linked through thiophene ring with triphenylamine is described. Introducing thiophene unit leads to extending the molecular absorption spectrum to the range of 330 nm–700 nm. The molecule showed the lowest unoccupied molecular orbital level (LUMO) of −3.80 eV and the highest occupied molecular orbital level (HOMO) of −5.60 eV. The X-ray Diffraction (XRD) spectra confirmed that the molecule self-assemble in the solid phase by edge-to-face aromatic interaction, and the addition of 1, 8-diiodooctane in the solvent can adjust its stacking, and thus improve the crystallinity and electron mobility. Solution-processed bulk-heterojunction organic solar cells constructed using the small molecule as acceptor and the polymer of PBDTTT-C-T as donor showed the best efficiency of 1.92%. Graphical abstract: Highlights: Small molecule based on perylenediimide, thiophene and triphenylamine was synthesized. The molecule self-assemble in the solid phase by edge-to-face aromatic interaction. 1, 8-diiodooctane could adjust the edge-to-face aromatic interaction of the molecule. Non-fullerene solar cells based on the molecule exhibited 1.92% efficiency.